Digital entrepreneurship in local government: Case study in Municipality of Fundão, Portugal. (October 2021) - Rodrigues, Margarida; Franco, Mário
Highlights: Digital entrepreneurship stimulates the formation of bonds and local networks, attracting investment and people. This study lies in identifying the digital processes adopted by local authorities associated with their governance. Strategic planning of cities supported by the axes of intelligence and sustainability. A change imposed on cities means that good governance practices must be the starting point. Abstract: Digital entrepreneurship is an inseparable axis of technological evolution and digitalization experienced in the twenty-first century, so the role played by the technological and related sectors requires the relevant investment of all economic and non-economic actors in places with administrative and political powers. Like any kind of entrepreneurship, digital entrepreneurship stimulates the formation of bonds and local networks, attracting investment and people. In addition, it stimulates the fight against depopulation in rural areas, such as the case studied here. The objective is to study local authorities' level of digitalization and their capacity to improve their technological and digital information systems, through a qualitative methodology, specifically the case study method. The results show the relevance of local actors becoming digital entrepreneurs, as this impacts on economic development and is a means to counter the negative aspects of geographical isolation verified in recent years.